East Java green tea methanolic extract can enhance RUNX2 and Osterix expression during orthodontic tooth movement in vivo - Putri I. Sitasari, - (JPPRes, 2020)
Context: Alveolar bone remodeling is important to achieve an optimal Orthodontic Tooth Movement (OTM). Runt-related transcription factor (RUNX2) and Osterix (OSX) expression are important for bone Remodeling. Green tea (Camelia sinensis) can enhancing bone remodeling. Aims: To investigate the effect of a methanolic extract of green tea ( MEGT) on the OSX and RUNX2 expression during OTM in Wistar rats. Methods: The experiment with post-test only and simple random a sampling was conducted. The samples consisted of twenty-eight Wistarr ats, which were then divided into 4 groups (n=7), negative control (CN)g roup, positive control (CP) group with OTM but without MEGT administration, group with OTM for 14 days and MEGT administrationf rom day 7 to day 14 (T1), group with OTM with MEGT administration for 14 days (T2). Nickle-titanium coil spring with 10 g/mm force was placed between the incisors and the maxillary molars. MEGT was collected from East Java and identified its principal metabolite by HPLC analysis. RUNX2 and OSX expression were analyzed by utilizing Immunohistochemical analysis. Analysis of Variance (ANOVA) was performed and then continued with least significant difference (p<0.05). Results: The highest RUNX2 and OSX expression were found in the tension side of group T2 with significant difference between groups (p<0.05). The principal metabolite of the extract was identified as epigallocatechin-3-gallate (EGCG). Conclusions: Post administration of a MEGT could increase RUNX2 and OSX expression in alveolar bone of OTM Wistar rats. Part of this action could be attributed to the presence of EGCG in the extract.